Components of a Financial Education Technology for Micro-entrepreneurs in Brazil - Lawrence, Nathaniel Archer (JSSE - Journal of Social Science Education, 2019)
Purpose: This article designs a pedagogy and scalable technological solution to provide Brazilian micro- and small enterprises with guidance in business management habitdevelopment. Approach: The study demonstrates the need for formalized micro-entrepreneurship training and, given general financial education programs’ poor performance, considers micro-entrepreneurs’ fundamental educational needs. Findings: The analysis provides three fundamental components to consider in microentrepreneurship training design: content utility, communication intelligibility, and material interactivity. Research implications: The proposed pedagogy and virtual trainer technology suggest further study and development of optimal approaches to content utility, communication intelligibility, and material interactivity to improve micro-entrepreneurial habit-development and economic development.